Functional Chicken Meatballs with Carrot Pomace Powder - Santhi, D.; Kalaikannan, A.; Elango, A.; Natarajan, A. (Journal of Meat Science, 2022)
This study was conducted to fortify low-fat chicken meatballs with dried carrot pomace as dietary fibre (DF) source and to assess the physicochemical and sensory properties. Carrot pomace was dried and made into powder. Emulsion-based low-fat chicken meatballs were prepared with the addition of carrot pomace powder (CPP) at levels of 1%, 2%, and 3%, over and above the amount of meat along with a control. In the physicochemical properties, there was no significant difference in the emulsion pH, product pH, and emulsion stability among the treatments. Product yield significantly (p≤0.01) increased with the addition of CPP at 2% and 3%. In sensory evaluation, the appearance score was significantly (p≤0.01) lowest for the 3% level. Juiciness, texture, and tenderness scores decreased with the addition of CPP where 3% level had the lowest scores. The flavour and overall acceptability scores significantly (p≤0.01) decreased with the addition of CPP where 1% and 2% had scores more the ‘moderately acceptable’ level and 3% had the lowest score which was only ‘slightly acceptable’. It is concluded that emulsion-based low-fat chicken meatballs could be fortified with dietary fibre content by the inclusion of carrot pomace powder up to a level of 2% without significantly affecting the sensory qualities.
Keywords: Carrot pomace powder; Chicken meatballs; Dietary fibre; Physico-chemical properties; Sensory Properties